Isolation, Identification and molecular characterisation of Mycoplasma isolates from small ruminant Mycoplsmosis of Karnataka state, India - BR, Sumathi; Sannegowda, Saritha N; Koppad, Sanganagouda; Gomes, Amitha Reena; Govindaiah, Kavitha; Marinaik, chandranaik B; Venkataramana , Sreevatsava (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Mycoplasmosis, the diseases caused by mycoplasma, are one of the challenging and continuous threats to small ruminant farming resulting in heavy morbidity (upto 100%), mortality (10-100%) and huge economic loss. In India there are only few published reports of mycoplasmosis masifestations in small ruminants. In the present study, attempts have been undertaken for the isolation, identification and molecular characterization of Mycoplasma isolates from suspected respiratory manifestations and mastitis cases small ruminants of Karnataka state, India. A total of 300 samples were collected from 180 goats and 80 sheep from different districts of Karnataka, India; 110 nasal swabs, 35 lungs and bronchial tissue, 50 lacrymal secretions from respiratory manifestations, 90 milk samples from contagious mastitis, 15 samples from joints abscess aspiration fluid were cultured on pleuropneumonia-like organisms (PPLOs) media for cultivation of Mycoplasma species. The genus and species were confirmed by genus and species-specific PCR. Further, sequencing and phylogenetic analysis were adopted to identify and classify the isolates. A total of 14 Mycoplasma isolates were isolated using PPLO broth and agar media with slight modifications in the composition, identified by growth pattern and microcolony morphology. Among these 7 isolates were confirmed as Mycoplasma capri, 4 isolates as M. agalectiae, and 3 isolates as M. arginine by genus and species-specific PCR. A purified isolates of M. capri, M. agalectiae and M. arginini was sequenced and phylogenetic analysis was carried out. The present study reveals the prevalent species of Mycoplasma associated with respiratory manifestation, mastitis and arthritis.